Changes in Thinking for Speaking: A Longitudinal Case Study. Issue 1 (February 2015) - Stam, Gale; Bylund, Emanuel; Athanasopoulos, Panos
ABSTRACT Cross‐linguistic research on motion events has shown that Spanish speakers and English speakers have different patterns of thinking for speaking about motion, both linguistically and gesturally (for a review, see Stam, 2010b). Spanish speakers express path linguistically with verbs, and their path gestures tend to occur with path verbs, whereas English speakers express path linguistically with satellites (adverbs or particles), and their path gestures tend to occur with satellite units. This article investigated whether a Spanish‐speaking English language learner's thinking for speaking patterns about motion exhibited continuous linguistic and gestural change in her L1 (Spanish) and L2 (English). The results indicate that the learner's gestural expression of path changed in both her L1 and L2, and her gestural expression of manner changed in her L2. This change suggests that manner, a pattern acquired in childhood, may not be resistant to change after all (Slobin, 1996; Stam, 2010b). The results have implications for the teaching of second and foreign languages.